Finding the sweet spot: Assembly and Glycosylation of the Dystrophin-Associated Glycoprotein Complex - Townsend, DeWayne (2014)
The dystrophin-associated glycoprotein complex (DGC) is a collection of glycoproteins that are essential for the normal function of striated muscle and many other tissues. Recent genetic studies have implicated the components of this complex in over a dozen forms of muscular dystrophy. Furthermore, disruption of the DGC has been implicated in many forms of acquired disease. This review aims to summarize the current state of knowledge regarding the processing and assembly of dystrophin associated proteins with a focus primarily on the dystroglycan heterodimer and the sarcoglycan complex. These proteins form the transmembrane portion of the DGC and undergo a complex multi-step processing with proteolytic cleavage, differential assembly, and both N- and O-glycosylation. The enzymes responsible for this processing and a model describing the sequence and subcellular localization of these events are discussed.